EP306 Is ultrasound KUB a useful investigation following radical hysterectomy?. (1st November 2019) - Haken, A; Sharma, A; Lim, K; Howells, R
Abstract : Introduction/Background: Incidence of iatrogenic ureteric injury during gynaecological surgery occurs in approximately 0.5–1.5% of cases with the majority occurring in benign cases. More than 70% are diagnosed during the post-operative period. However radical hysterectomy for malignancy significantly increases the risk of ureteric injuries (between 5–30%) and complications related to it. In view of this, the local guidelines at University Hospital of Wales recommend removing the urinary catheter at day 7 post-operatively, after an ultrasound of the kidneys, ureters and bladder (US KUB) to ensure there are no occult injuries. Methodology: The aims were to determine: if all patients undergo KUB imaging following radical hysterectomy; incidence of ureteric injury following radical hysterectomy for oncology patients. Retrospective audit of online patient records and clinical notes for all patients undergoing radical hysterectomy between January 2017 and October 2018 at University Hospital of Wales. Data collection and analysis performed using Microsoft Excel Version 16. Results: A total of 37 radical hysterectomies were performed, 86% (n=32) for cervical cancer. 92% (n=34) patients underwent US KUB (65% of which occurred on day 7 [n=22]; 24% [n=8] by day 10 with delay due to Public Holidays in 3 cases; and 12% [n=4] prior to day [AS1] 7, 2 of which were to exclude suspected post-operative complications). Of all US KUB performed 91% (n=31) were normal, and 6% (n=2) showed mild hydronephrosis only and one patient required a CT urogram for clarification. No urinary tract injuries were noted. Conclusion: The majority of patients had imaging at the appropriate time post-operatively. There were no urinary tract injuries identified with the US KUB however where suspicion was raised further investigation was carried out to exclude injuries. Hence US KUB is a simple yet useful tool, without risk of radiation exposure, to detect injuries in the immediate post-operative period and deal with them. Disclosure: Nothing to disclose.